Contact problem for the autofrettage of thick cylinders - Lvov, Gennadiy; Lysenko, Sergey (Miskolc university press, 2002)
The autofrettage of thick-walled cylinders with variable thickness is considered on the basis of a variational formulation of the corresponding elastic-plastic contact problem. The numerical solution is determined by the use of the finite element method. We have chosen a material model which takes kinematic hardening and the ideal Baushinger effect into account. The optimum geometric parameters for the bandage and the initial gap are both determined in a way that a favorable distribution of residual stresses will develop and the bandage is removed after unloading.
Keywords: autofrettage; finite element method; contact problem; residual stresses